A Maize (E)-β-Caryophyllene Synthase Implicated in Indirect Defense Responses against Herbivores Is Not Expressed in Most American Maize Varieties - Köllner, Tobias G. (American Society of Plant Biologists, 2008)
The sesquiterpene (E)-β-caryophyllene is emitted by maize (Zea mays) leaves in response to attack by lepidopteran larvae like Spodoptera littoralis and released from roots after damage by larvae of the coleopteran Diabrotica virgifera virgifera. We identified a maize terpene synthase, Terpene Synthase 23 (TPS23), that produces (E)-β-caryophyllene from farnesyl diphosphate. The expression of TPS23 is controlled at the transcript level and induced independently by D. v. virgifera damage in roots and S. littoralis damage in leaves. We demonstrate that (E)-β-caryophyllene can attract natural enemies of both herbivores: entomopathogenic nematodes below ground and parasitic wasps, after an initial learning experience, above ground. The biochemical properties of TPS23 are similar to those of (E)-β-caryophyllene synthases from dicotyledons but are the result of repeated evolution. The sequence of TPS23 is maintained by positive selection in maize and its closest wild relatives, teosinte (Zea sp) species. The gene encoding TPS23 is active in teosinte species and European maize lines, but decreased transcription in most North American lines resulted in the loss of (E)-β-caryophyllene production. We argue that the (E)-β-caryophyllene defense signal was lost during breeding of the North American lines and that its restoration might help to increase the resistance of these lines against agronomically important pests.